A Mononuclear Manganese Complex of a Tetradentate Nitrogen Ligand – Synthesis, Characterizations, and Application in the Asymmetric Epoxidation of Olefins. Issue 33 (8th October 2014) - Shen, Duyi; Miao, Chengxia; Wang, Shoufeng; Xia, Chungu; Sun, Wei
Abstract: A new chiral manganese complex (C1 ) bearing a tetradentate nitrogen ligand containing chiral bipyrrolidine and benzimidazole moieties was prepared. The structure ofC1 was confirmed by ESI‐MS and crystallography. This manganese complex is an active catalyst for the asymmetric epoxidation of various olefins with excellent conversion (up to 99 %) and high enantiomeric excess (up to 96 %  ee ) with hydrogen peroxide as the oxidant in the presence of 2‐ethylhexanoic acid or acetic acid. Compared with previous structurally similar manganese complexes with different diamine backbones (C2, cyclohexanediamine;C3, diamine fromL ‐proline), C1 showed improved asymmetric induction, especially for simple olefins such as styrene derivatives and substituted chromene. The possible reasons for the improvement of the ee values are discussed in the text on the basis of the crystal structures of the manganese complexes. Abstract : A chiral manganese complex bearing a tetradentate nitrogen ligand with chiral bipyrrolidine and benzimidazole moieties is an active catalyst for the asymmetric epoxidation of various olefins with excellent conversions (up to 99 %) and up to 96 %  ee with hydrogen peroxide as the oxidant in the presence of 2‐ethylhexanoic acid or acetic acid.